2020
DOI: 10.3390/jcm9082343
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Sectional Retrospective Study of Non-Splenectomized and Never-Treated Patients with Type 1 Gaucher Disease

Abstract: Patients with type 1 Gaucher disease (GD1) present thrombocytopenia, anemia, organomegaly, and bone complications. Most experts consider that the less aggressive forms do not require specific treatment. However, little is known about the disease course of these forms. The objective of this cross-sectional retrospective study was to compare the clinical, radiological, and laboratory characteristics of patients with less severe GD1 at diagnosis and at the last evaluation to identify features that might lead to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
0
6
2
Order By: Relevance
“…A Gaucher outcome survey involved 1209 patients with GD reported the overall treatment (1209, 73.4%) and different treatment rates in countries [the UK (119, 93.3%), Israel (536, 63.6%), the US (380, 82.6%), rest of the world (174, 69.5%)] [ 45 ]. In this study, 8 of the 49 patients (16.3%) were never treated, while 83.7% get treated, and 10 (20.4%) of patients undergone splenectomy, which was higher than previous research (8.7–13.3%) [ 2 , 45 ]. Besides, other studies have also shown a significant proportion of patients (e.g., asymptomatic or mildly affected) never accessed medical attention or required treatment [ 46 , 47 ].…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…A Gaucher outcome survey involved 1209 patients with GD reported the overall treatment (1209, 73.4%) and different treatment rates in countries [the UK (119, 93.3%), Israel (536, 63.6%), the US (380, 82.6%), rest of the world (174, 69.5%)] [ 45 ]. In this study, 8 of the 49 patients (16.3%) were never treated, while 83.7% get treated, and 10 (20.4%) of patients undergone splenectomy, which was higher than previous research (8.7–13.3%) [ 2 , 45 ]. Besides, other studies have also shown a significant proportion of patients (e.g., asymptomatic or mildly affected) never accessed medical attention or required treatment [ 46 , 47 ].…”
Section: Discussioncontrasting
confidence: 72%
“…Meanwhile, the more objective support caregivers received, the higher the health-related quality of life of GD caregivers. Due to the nervous system involvement of type 2 GD [ 2 ], it is challenging to take care of patients with type 2 Gaucher 's disease. Health decision-makers and clinicians should take action to recover the life function of type 2 GD patients and give nursing suggestions to the caregivers of patients with Gaucher 's disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40]. In this study, 8 of the 49 patients (16.3%) were never treated, while 83.7% get treated, and 10 (20.4%) of patients undergone splenectomy, which was higher than previous research (8.7%-13.3%) [2,40].…”
Section: Discussioncontrasting
confidence: 66%
“…Gaucher disease (GD), an ultra-rare multi-organ involvement, inherited recessive enzyme de ciency [1,2], is slowly progressing. Its standardized incidence and prevalence among the general population worldwide vary from 0.30 to 5.80 per 100,000 population, respectively; however, the initial estimate was 0.25 to 1.24 per 100,000 population [3,4] with hundreds of patients diagnosed with GD in China.…”
Section: Introductionmentioning
confidence: 99%